The Usage of Crumb Rubber Filtration and UV Radiation for Ballast Water Treatment - Trika Pitana; Maya Shovitri; Haris Nur Fauzi (Institut Teknologi Sepuluh Nopember, 2017)
This research is aimed to build ship’s ballast water treatment prototipe that used to inactivate microbial water patogen in ballast water to produce unpolluted ballast water that can be standardised by IMO Ballast Water Management Convention. A simple concept that used in the development of this prototype is by draining ballast water with capacity at 5 lpm, 10 lpm and 20 lpm into alternative filtration crumb rubber and UV reactor. In the filtration process using crumb rubber, ballast water will be filtered with the precision filtration up to 50 micron, while in the UV reactor ballast water will be illuminated by UV-C with maksimum dose 16,58 mW/cm2. Finally,the study shows the performance of alternative filtration of crumb rubber and UV-C irradiation on microbial water phatogen, and at what UV-C dose ballast water treatment prototipe can inactivate microbial water phatogens, which are complying with IMO Ballast Water Management Convention ANNEX D.This research is aimed to build ship’s ballast water treatment prototipe that used to inactivate microbial water patogen in ballast water to produce unpolluted ballast water that can be standardised by IMO Ballast Water Management Convention. A simple concept that used in the development of this prototype is by draining ballast water with capacity at 5 lpm, 10 lpm and 20 lpm into alternative filtration crumb rubber and UV reactor. In the filtration process using crumb rubber, ballast water will be filtered with the precision filtration up to 50 micron, while in the UV reactor ballast water will be illuminated by UV-C with maksimum dose 16,58 mW/cm2. Finally,the study shows the performance of alternative filtration of crumb rubber and UV-C irradiation on microbial water phatogen, and at what UV-C dose ballast water treatment prototipe can inactivate microbial water phatogens, which are complying with IMO Ballast Water Management Convention ANNEX D.